A [(M2)6L8] metal–organic polyhedron with high CO2 uptake and efficient chemical conversion of CO2 under ambient conditions. Issue 44 (11th May 2022) - Liu, Li-Hua; Liu, Lin; Chi, Hao-Ran; Li, Chen-Ning; Han, Zheng-Bo
Abstract : A new rhombic dodecahedron Cu–MOP with high absorption of CO2 has been successfully synthesized, and it exhibits excellent performance in chemical fixation of CO2 into cyclic carbonates under ambient conditions. Abstract : A new metal–organic polyhedron with a high surface area of 407 m 2 g −1, possessing high CO2 uptake, is reported, which is synthesized using 4-connected Cu2 (CO2 )4 paddle-wheel moieties and 3-connected semi-rigid tripodal carboxylates. This material possesses a high density of Cu(ii ) Lewis acidic sites and demonstrates excellent performance as a heterogeneous catalyst for the chemical fixation of CO2 into cyclic carbonates under ambient conditions.